Sessile droplet evaporation on patterned surfaces - Ng, Aaron Chin Liang (Nanyang Technological University, 2023)
In this study, the evaporation behaviour between suspension fluids and water droplets has been investigated on different substrates. The sizes of particles in the suspension fluids increases by a factor of ten sizes from 0.05μm, 0.5μm and 6μm. The substrates used are Al2O3, TiO2 flat and a patterned micro pyramid substrate. For the patterned substrate, a 0º and 45º line of sights are used. Both offer different properties such as hydrophobicity. As such, the interaction and behaviour of the fluid are experimented with using a combination of microscopy and a high-speed camera. Specifically, the dimensions and contact angles of the droplets are taken throughout the evaporation phase. Thereafter, a surface roughness profile is developed to detail the exact deposition using a confocal microscopy. First, DI water droplets provide a good base line for the substrate properties and a comparator for the suspension fluid droplets. The results show the substrates differs in hydrophobicity. However, fluid with colloidal particles overall increases the contact angle and decreases the dimensions of the contact line which gave an overall increase in hydrophobicity. For the patterned substrate at Ls0º, it increases further in hydrophobicity as the micro pyramid structures acts as barrier. This is different at Ls45º where it was not as hydrophobic as Ls0º. There were inherent directional properties of the micro pyramid substrate which correlates to the wetting properties. Furthermore, the observation of the final dried deposited pattern was that the outward capillary flow becomes less dominant as the particle sizes increases. With a bigger particle size, the coffee-ring pattern becomes less dominant which slowly transitions into a uniform pattern. This study provides important insights into the mechanisms of how suspension fluids in the same concentration behaves in the presence of different substrates with different properties.